REPRENTASI PERUNDUNGAN PADA VIDEO MUSIK BABYMETAL – IJIME, DAME, ZETTAI- ANALISIS SEMIOTIKA ROLAND BARTHES - Kusumandyoko, Tri Cahyo (Universitas Komputer Indonesia, 2021)
ABSTRACT. Bullying is a negative action carried out by an individual or group that intentionally causes harm to others, which is carried out repeatedly. Indonesian people are increasingly carrying out bullying during this pandemic through electronic media. This is due to the high level of depression in Indonesian society during the pandemic, 64.8% (Sagita, 2020). The bullying eradication campaign has also been carried out by various groups, one of which is a metal musician from Japan, Babymetal. Babymetal has one single titled Ijime, Dame, Zettai; where the word â€œIjimeâ€ literally means bullying, Babymetal advised its fans to unite and not bully others. The music video released on Babymetal's youtube channel caught the attention of many people and has been viewed 27 million times. This research was conducted to understand the message and meaning of the music video using Roland Barthes semiotic analysis. The analysis results are presented descriptively by researchers using qualitative methods with data analysis techniques using four stages of design review so that messages and meanings will be obtained the Indonesian people can understand that to eradicate bullying.. Keywords : Bullying, Music Video, Babymetal, Metal, Barthes, Semiotic.